FINANCIAL DISCIPLINE: A SURVEY OF ENTREPRENEURS’ PERSPECTIVES IN SOUTH SULAWESI - Abdul Rakhman (Universitas Hayam Wuruk Perbanas, 2011)
This article emphasizes on exploring a variety way of South Sulawesi’s entrepreneurs to im- plement financial discipline in organizing their businesses appropriately. In addition, this research attempts to investigate factors which need to be considered by entrepreneurs to achieve financial discipline. It was conducted in South Sulawesi with 250 respondents. The data were collected and analyzed by using structured Equation Modeling. The participants’ responses indicate that most of entrepreneurs intent to practice financial management and consider financial commitment in their effort in order to achieve financial discipline. The findings show that capability of entrepreneurs and their individual characteristics have af- fected financial commitment and financial discipline but it does not affect intention to prac- tice financial management. The role of government only affects financial commitment signifi- cantly but it does not affect intention to practice financial management and financial disci- pline. Environment influences, significantly, the intention to practice financial management and financial commitment but it did not affected financial discipline. Furthermore, leader- ship affects, significantly, the financial commitment, intention to practice financial manage- ment and financial discipline. Last of all, financial commitment also affects intention to prac- tice financial management but it does not affect financial discipline, whereas intention to practice financial management affects financial discipline